ESP in the Light of the Globalisation Process : A Linguistie Overview - Benyelles, Radia Benmansour (جامعة قاصدي مرباح - ورقلة, 2010)
The globalisation of the world is systematic process pushed by Anglo-American strategies. Accordingly the English language becomes the most taught foreign language all over the world. In the Arab world, English has become the language of higher communication in the field of science and technology; post-graduate education; economic affairs; international banking and trade. Thus, the language is getting entranced in the Arab world especially after the second Gulf War and the defeat of Iraq. In the Arab region, English is occupying more and more a room in language use. It is gaining more and more territory from the native language. The international status of English, makes it necessary utilize English in a range of social and thematic areas. The main concern of the linguist is to try to describe the ‘special Englishes’ at all levels of language, including both its diachronic and synchronic dimensions.
Keywords: العولمة